Prediction of Suicidality According to Serum Folate Levels in Depressive Patients Receiving Stepwise Pharmacotherapy - Kim, Jae-Min; Kim, Ha-Yeon; Lee, Hee-Joon; Kim, Ju-Wan; Kang, Hee-Ju; Kim, Sung-Wan; Shin, Il-Seon; Chun, Byeong Jo; Stewart, Robert (Frontiers in Psychiatry, 2021)
Background: The effects of serum folate levels on suicidal behavior, strongly associated with depression, have not been investigated. Therefore, this study investigated the associations between serum folate levels and suicidal behavior in patients with depressive disorders. Methods: Serum folate levels were measured at baseline in 1094 patients with depressive disorder, 884 of whom were followed during a 12-month period of stepwise pharmacotherapy. Suicidal behaviors evaluated at baseline were i) previous suicide attempt and ii) baseline suicidal severity; behaviors evaluated at follow-up were iii) increased suicidal severity and iv) fatal/non-fatal suicide attempt. Associations of serum folate levels with four types of suicidal behaviors were analyzed using logistic regression models after adjustment for relevant covariates; they were also examined using area under receiver operating characteristic (AUROC) curve analyses. Results: Reduced serum folate levels (< 6.0 ng/mL) were independently associated with all four types of suicidal behaviors. AUROC curve analyses indicated that discriminant or prognostic values of reduced serum folate levels were fair for fatal/non-fatal suicide attempt during follow-up, whereas they were modest for previous suicide attempt, baseline suicidal severity, and increased suicidal severity. Conclusions: Serum folate levels could serve as a biomarker of suicidal behavior in depressive patients. However, it should be used as an adjunct rather than a substitute for prediction of suicidal behavior considering its low prognostic values. Further replication studies are needed for its clinical utilization.